Kombinasi Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) dan PIPRECIA dalam Seleksi Penerimaan Barista - Sintaro, Sanriomi; Setiawansyah, Setiawansyah (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2024)
Barista acceptance selection is a crucial stage in building a quality team in the coffee industry. This process not only looks for individuals with technical skills in processing coffee, but also emphasizes other aspects such as communication skills, customer service, and appearance. The combination of MOORA and PIPRECIA methods can be used to optimize several goals at once by considering the ratio between positive and negative solutions in determining the best alternative based on several criteria. This study aims to select barista acceptance by applying a combination of MOORA and PIPRECIA methods based on the criteria used, namely ability, knowledge, experience, communication, and appearance. So that the results of the combination of MOORA and PIRRECIA methods will be a recommendation for management in selecting barista acceptance. The ranking results for rank 1 with the final value of MOORA optimization of 0.428 were obtained by Yanto, rank 2 with the final value of MOORA optimization of 0.423 was obtained by Ridho, and rank 3 with the final value of MOORA optimization of 0.414 was obtained by Antoni. The benefit of this study will be a recommendation for coffee shop owners in conducting barista selection using a decision support system model. Future research may add other criteria such as barista education and training.